Relationship between cerebrospinal fluid flow, ventricles morphology, and DTI properties in internal capsules: differences between Alzheimer's disease and normal-pressure hydrocephalus. (October 2014) - Daouk, Joël; Chaarani, Bader; Zmudka, Jadwiga; Capel, Cyrille; Fichten, Anthony; Bouzerar, Roger; Gondry-Jouet, Catherine; Jouanny, Pierre; Balédent, Olivier
Background: Normal-pressure hydrocephalus (NPH) and Alzheimer's disease (AD) have some similar clinical features and both involve white matter and cerebrospinal fluid (CSF) disorders. Purpose: To compare putative relationships between ventricular morphology, CSF flow, and white matter diffusion in AD and NPH. Material and Methods: Thirty patients (18 with AD and 12 with suspected NPH) were included in the study. All patients underwent a 3-Tesla MRI scan, which included phase-contrast MRI of the aqueduct (to assess the aqueductal CSF stroke volume) and a DTI session (to calculate the fractional anisotropy [FA] and apparent diffusion coefficient [ADC]) in the internal capsules). Results: FA was correlated with ventricular volume in the suspected NPH population ( P  < 0.001; rs  = 0.88), whereas the ADC was highly correlated with the aqueductal CSF stroke volume in AD ( P  < 0.001; rs  = 0.79). Conclusion: Although AD and NPH both involve CSF disorders, the two diseases do not have the same impact on the internal capsules. The magnitude of the ADC is related to the aqueductal CSF stroke volume in AD, whereas FA is related to ventricular volume in NPH.